PENGEMBANGAN MODEL PEMELAJARAN CERITA RAKYAT MELALUI COPYWRITING - Apriola, Vinna (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
Development model this folklore Iesson is background by writer desire which have profession as teacher to bear special Iesson model this subject and of a kind, bearing better Iesson condition in student easiness and class to fond of to read folklore.This research And development aim to give information about existence one of effective Iesson model in course of folklore Iesson to Indonesian teacher, and as positive input in development model folklore Iesson for the sake of furthermore. This Research type is research qualitative using method R&D (Research And Development). Research checking and developing folklore Iesson model in class.This Research instrument is interview do not the structure, and respon assessment enquette addressed to coleage and student as valid determinant of product, and also the field note hit things that happened in product test in class.This Research data is product in the form of substance teach to print containing of development execution guide model folklore Iesson of through copywriting which tried with instrument. Result obtained from research product test applied in class XI IPS 3 SMA Plus Negeri 7 Kota Bengkulu in teaching year 2012 on Wednesday, 16 May 2012 beating 08.45-10.15 WIB is effective, according to, and draw.